STUDI PERENCANAAN ULANG DINDING PENAHAN PADA HULU BENDUNG KRAMAT KECAMATAN TUMPANG KABUPATEN MALANG - Kiki Frida Sulistyani; Kadir Lebao (Universitas Tribhuwana Tunggadewi Malang, 2016)
This study aimed to performre-planning study on there taining wall of Kramat Weir, Tumpang District, Malang Regency. This planning wasused to over come the river bed scour resulting land slide and collapse of retaining walls at the up stream weir. Before planning the retaining wall, firstly it was performed hydrologican alysisconsisted of collecting rainfall data, rainfall analysis designed by Log Pearson Type III method, and calculating the design flood dischargeby using Nakayasu Method. Hydrological analysis resulted that flood discharge of 50 years period plan(Q50years) was 73.636m3/sec;with water level of2.50mabove weir plan. From the calculation results it was obtained that water level above weir could be planned the dimensions of retaining wall planned with building height (h) = 4.5 m (from foundation base), talud slope (z) 1:0.2 (v:h), depth offoundation (Df) = 1m, width of foundation base (b) = 2.50 m to the type of masonryconstruction. Analysis of stability of soil to capacity was less than robust ground i.e. Qallowed17.827t/m2(safe), while stability against sliding was 2.205 and roll was 1.815 with the safety number which was greater than 1.5 (safe). It can be concluded that there taining wall planis stable.